Mediating meanings: conservation of the Staffordshire Hoard. Issue 3 (October 2016) - Castriota, Brian
Abstract Since the Staffordshire Hoard's discovery in 2009, soil removal has been carried out over several years by conservators working with the Staffordshire Hoard Conservation Project at the Birmingham Museum and Art Gallery. As a case study, this essay examines the practical and philosophical considerations that arose during the author's cleaning of object K1195, a gold and garnet cloisonné sword pommel cap, in 2012. Cleaning – understood as a culturally determined intervention that enacts permanent change on an object – is a frequent subject of debate within cultural heritage preservation. This essay considers the cleaning of an archaeological object with respect to its ontological status, borrowing concepts employed in the conservation of modern and contemporary works of art.